2018
DOI: 10.1029/2018ja025660
|View full text |Cite
|
Sign up to set email alerts
|

The Distributions of Iron Average Charge States in Small Flux Ropes in Interplanetary Space: Clues to Their Twisted Structures

Abstract: Small flux ropes (SFRs) have been studied for decades, but their source regions and formation mechanisms are still under debate. In this study, we focus on the formation mechanism of the twisted structures of SFRs. Current research on magnetic clouds suggests five‐type distributions of the time structure of iron average charge states (Q), which imply different formation mechanisms of twisted structures. We use a similar method to identify the Q types of 25 SFRs. However, only four of these five types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 70 publications
(158 reference statements)
0
17
0
Order By: Relevance
“…Feng and Wang found that SIMFRs exhibit the same high-charge-state signatures as MCs, and hot materials within SIMFRs must be heated by related flares in the corona[43]. These findings provide reliable evidence for the conjecture that SIMFRs and MCs havethe same coronal origins and thatSIMFRs are interplanetary counterparts of small CMEs[43].Huang et al[51]…”
mentioning
confidence: 85%
“…Feng and Wang found that SIMFRs exhibit the same high-charge-state signatures as MCs, and hot materials within SIMFRs must be heated by related flares in the corona[43]. These findings provide reliable evidence for the conjecture that SIMFRs and MCs havethe same coronal origins and thatSIMFRs are interplanetary counterparts of small CMEs[43].Huang et al[51]…”
mentioning
confidence: 85%
“…The end result is that the ionization fractions do not vary any longer, i.e., freeze-in. This means that the ionic fractions measured in situ are largely determined by the physical parameters near the Sun where freeze-in occurs (Rakowski, Laming, and Lepri, 2007;Lynch et al, 2011;Gruesbeck et al, 2011;Gruesbeck, Lepri, and Zurbuchen, 2012;Song et al, 2015b,c), which have been further used to infer the eruption process of flux ropes (Song et al, 2016;Wang et al, 2017;Huang et al, 2018). It should be noted that the different structures of CMEs have different freeze-in history (Gruesbeck, Lepri, and Zurbuchen, 2012;, which leads to the complex nature of ICMEs and makes the interpretation of ions in situ less straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…The charge states within ICMEs are frozen-in near the Sun [33], and the relative abundances of elements with different first ionization potentials (FIPs) are different obviously in the corona and photosphere [34,35]. As the composition does not alter during CME propagation to 1 AU and beyond [36], the in situ data are also employed to analyze the MFR formation [28,37,38] and plasma origin [39,40] of CMEs. So far, the most complete composition data of ICMEs are provided by the solar wind ion composition spectrometer (SWICS) aboard Advanced Composition Explorer (ACE) and Ulysses, which can provide the charge states and elemental abundances of ∼10 elements [41].…”
Section: Introductionmentioning
confidence: 99%